Strategic plan for developing nursing professional standards at an university hospital, Rio de Janeiro, Brazil - Cruz, Isabel Cristina Fonseca da; Larrúbia, Eliel de Oliveira; Azavedo, Neuza Maria de; Ribeiro, Marly Rodrigues; Rocha, Ana Maria Rongel; Moraes, Cláudia de Souza; Silva, Sonia Regina de Oliveira; Costa, Cristiane Maria Amorim (Online Brazilian Journal of Nursing, 2002)
At the University Hospital of the University of Rio de Janeiro State (HUPE/UERJ), the Nursing Coordination analysed the social context and the stakeholders of health assistence, and identified a problem to address: a change shift in the focus from the clien and student to the institution itself.Objective:To achieve the vision of a 24/7 nursing care, centered in the client and based on scientifc evidence, a strategic plan was developed to establish nursing professional standards.Method:As an instrument of social management, this Strategic Plan 2002-2003 represents the process of assessment, diagnosis, planning, and evaluation of the nursing managers to improve the quality of care at HUPE/UERJ.Results:It put emphasis on maximizing nursing performance (redesign activities and functions), enhancing client satisfaction, and producing therapeutic results. To realize the Nursing Coordination vision, a plan of goals, strategies, responsibilities, and status monitoring has been set forth for the period from May 2002 through December 2003.Final considerations: As an ongoing process, this strategic plan will be a framework to continually reassess the goals and strategies, which were linked to the hospital, and to update the plan ensuring that the focus of the nursing action is the client and the education of undergraduate and graduate student.